2002
DOI: 10.1002/srin.200200026
|View full text |Cite
|
Sign up to set email alerts
|

Light-weight steels based on iron-aluminium - influence of micro alloying elements (B, Ti, Nb) on microstructures, textures and mechanical properties

Abstract: The influence of the micro alloying elements B, Ti and Nb on the recrystallization texture and mechanical properties of iron aluminium light‐weight steels, particularly with reference to their improved deep drawing properties was investigated. Depending on the combination of the alloying elements the microstructures of the investigated micro alloyed Fe‐6Al steels are influenced by grain refinement. Likewise, variable combinations of micro alloying elements differently affect the texture. Generally, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…It has been known that the density of steels can be reduced by the addition of Al and therefore there is a growing interest in developing Al containing steels, so-called lightweight or low density steels [1][2][3]. Depending on the type of major constituent phase, these lightweight steels can be classified into several types; ferritic [1,[4][5][6][7][8][9][10][11][12][13], austenitic [14,15] and ferrite-austenite duplex types [9,16,17]. Having lower mechanical properties compared to those of austenitic or duplex steels [2], ferritic lightweight steels have received less attention than other types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known that the density of steels can be reduced by the addition of Al and therefore there is a growing interest in developing Al containing steels, so-called lightweight or low density steels [1][2][3]. Depending on the type of major constituent phase, these lightweight steels can be classified into several types; ferritic [1,[4][5][6][7][8][9][10][11][12][13], austenitic [14,15] and ferrite-austenite duplex types [9,16,17]. Having lower mechanical properties compared to those of austenitic or duplex steels [2], ferritic lightweight steels have received less attention than other types.…”
Section: Introductionmentioning
confidence: 99%
“…Having lower mechanical properties compared to those of austenitic or duplex steels [2], ferritic lightweight steels have received less attention than other types. Although there has been no systematic study on the effect of grain size on the mechanical properties of ferritic lightweight steels, analyses of their microstructures available in literature show that their grain sizes are rather coarse (over 40 µm) in final products [5][6][7][8][9][10][11][12]. Unlike the austenitic and duplex lightweight steels, mechanical properties, particularly ductility, of ferritic lightweight steels would be strongly dependent on the grain size due to their bcc structure.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that C content in Al-containing ferritic steels should be minimized to avoid the possible formation of ordered carbides, Fe 4Ày Al y C x (0.8 £ y £ 1.2; 0 £ x £ 1), 41 which are detrimental to sheet formability. This has led to the development of high Al-containing low-density IF steels 20 with the addition of a stoichiometric amount of stabilizing elements such as Ti, similar to traditional IF steels.…”
Section: Steels According To Phase Constitutionmentioning
confidence: 99%
“…However, such substitutions are not straightforward if other effects and interactions among alloying elements are to be taken into account. Therefore, incessant efforts have been taken throughout the development of steels, both by industries and academies, to modify steel with leaner chemistry [9][10][11][12][13] and/or more economical process routes. 14,15) Nevertheless, competing and/or conflicting alloying effects on alloy cost versus alloy properties, make the empirical alloy design approach even more inefficient and hence a system optimization of the performance/price ratio in alloy design become an even more attractive target.…”
Section: Introductionmentioning
confidence: 99%